Friday

December 19, 2014

December 19, 2014

Posted by **123university** on Tuesday, January 5, 2010 at 9:22pm.

cos^2x- 2cosx+1

4cos^2x-1

- trig -
**Damon**, Tuesday, January 5, 2010 at 10:28pmcall z = cos x

z^2 -2z +1

(z-1)(z-1)

so

(cosx-1)(cosx+1)

4z^2-1

(2z-1)(2z+1)

(2cosx-1)(2cosx+1)

**Answer this Question**

**Related Questions**

Math - Solving Trig Equations - What am I doing wrong? Equation: sin2x = 2cos2x ...

Math - Solving for Trig Equations - For the following equation, why cannot I not...

Trig - prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= ...

trig--power reducing formulas - Having trouble with this problem: Rewrite the ...

Math - Trig - Double Angles - Prove: cos4x = 8cos^4x - 8cos^2x + 1 My Attempt: ...

trig - cos@-4SIN@=1 then sin@+4cos@=

TRIG - Factor 4cos^2x+4cosx-1=0

Trig - Factor 4cos^2x+4cosx-1=0

Trig - (cos^2t+4cos^2+4)/(cost+2)=(2sect+1)/sect

Trig - Prove (cos^2t+4cos^2+4)/(cost+2)=2sect+1)/sect